Lactate-driven macrophage polarization in the inflammatory microenvironment alleviates intestinal inflammation - Zhou, Hai-Cun; Yu, Wen-Wen; Yan, Xin-Yan; Liang, Xiao-Qin; Ma, Xiu-Feng; Long, Jian-Ping; Du, Xiao-Yan; Mao, Hong-Yan; Liu, Hong-Bin (Frontiers in Immunology, 2022)
Background：Lactate has long been considered as an intermediate material in carbon metabolism, but recently accumulated evidence suggests that lactate has unique biological activities. In previous studies, lactate signaling was found to inhibit inflammation. It has also been found that lactic acid can regulate the transformation of pro-inflammatory macrophages and anti-inflammatory macrophages in vitro. However, So far, there has been no report on whether lactic acid can alleviate inflammation and injury in vivo by promoting macrophage polarization to regulate the inflammatory immune microenvironment. Methods：In order to evaluate the anti-inflammatory effect of lactic acid, LPS-induced activated RAW 264.7 macrophages were cultured with lactic acid in vitro，the phenotypic transformation of macrophages and the expression of inflammatory signals were detected, also the expression of inflammatory factors in the cell supernatant was detected. Then the mouse model of DSS-induced colitis was constructed, and local lactate therapy was administered. We detected colonic tissue injury by histopathology, intestinal mucosal barrier injury, serum levels of pro-inflammatory factors and anti-inflammatory factors in mice, and detected the phenotypic transformation of macrophages in colon tissue. Results: In vitro, increasing lactate concentration promoted the transformation of activated macrophages to M2 phenotype, decreased the expression levels of TLR4-mediated NF-κB signaling proteins in activated macrophages, and decreased the expression levels of inflammatory factors. In the DSS-induced colitis mouse model, lactic acid promoted the phenotypic transformation of macrophages in colonic tissue, reduced inflammation and organ damage in colitis mice, inhibited the activation of TLR4/NF-κB signaling pathway, reduced the level of pro-inflammatory factors in serum, increased the level of anti-inflammatory factors, promoted the repair of intestinal mucosal barrier and finally reduced the severity of colitis. Conclusions：Lactate inhibited the expression of TLR/NF-κB inflammatory signals and the production of pro-inflammatory factors by regulating the polarization of macrophages in the inflammatory microenvironment, promoted the repair of intestinal mucosal barrier and protected intestinal tissue in inflammation, and it has no toxic and side effects. Therefore, lactate may be a promising and effective drug for the treatment of inflammation through immunometabolic regulation.